2016
DOI: 10.1063/1.4966158
|View full text |Cite
|
Sign up to set email alerts
|

Thermal efficiency of a solar power system in a collective residential structure based on performance tests

Abstract: Here, we evaluated the efficiency of a solar domestic hot water system in a dormitory in Rzeszow. Radiance exposure was analyzed based on information obtained from an online database (the meteorological station in Rzeszow-Jasionka). The mean seasonal and annual solar irradiation of a flat surface and surfaces inclined at 30°, 45°, and 60° from the horizontal plane in Rzeszow were determined. The mean monthly irradiation was compared with that in selected European cities based on the Photovoltaic Geographical I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The ground source heat pump is used only during heating season. Domestic hot water out of the space heating system is accomplished via the solar thermal system operation, which operates very effectively in Polish conditions [18,24]. From May until the end of September the thermal solar energy system can cover all DHW heating demand.…”
Section: Final Heating Energy Consumption Of the Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ground source heat pump is used only during heating season. Domestic hot water out of the space heating system is accomplished via the solar thermal system operation, which operates very effectively in Polish conditions [18,24]. From May until the end of September the thermal solar energy system can cover all DHW heating demand.…”
Section: Final Heating Energy Consumption Of the Buildingmentioning
confidence: 99%
“…Polish conditions [18,24]. From May until the end of September the thermal solar energy system can cover all DHW heating demand.…”
Section: Final Heating Energy Consumption Of the Buildingmentioning
confidence: 99%
“…Thus, the intensive research in the field of solar thermal collectors has had the aim to improve the specification of solar thermal collectors to increase their efficiency within approximately 20 years [24][25][26][27]. However, they still have a higher initial cost than conventional water heating systems, this being a major obstacle to its adoption by low income families and leading to the need for an economic analysis of this system.…”
Section: Solar Water Heating Systemsmentioning
confidence: 99%
“…Economic efficiency expressed by the payback time of active SWH system investment differs depending on the solar system producer and the fuel/heat source that is substituted, and can range from 6 to 16 years [35]. From the economic cost-effectiveness analysis of SWH systems, Sawicka-Chudy et al (2016) found that the simple payback time of modernization is around 16 years [24]. Argiriou et al (1997) found a better cost-benefit ratio, a low payback period for SWH systems and a reduction of CO 2 emissions by 40% in Greece [36].…”
Section: Solar Water Heating Systemsmentioning
confidence: 99%